Google Sites como herramienta digital para el aprendizaje de Biología Vegetal con los estudiantes de tercer semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Acan Inga, Nataly Rocio (2025)
The research work is about the digital tool "Google Sites" as an aid in the learning process, it was carried out at the National University of Chimborazo, in the Faculty of Education, Humanities and Technologies. The objective is to propose Google Sites as a digital tool for the learning process of Plant Biology with third semester students of the Degree in Pedagogy of Experimental Sciences Chemistry and Biology, the methodology is quantitative approach, the design is non-experimental, by the descriptive level, by the objective it is Basic, by the place it is field and bibliographic, type of cross-sectional study, the method was synthetic and inductive. The population was 32 students, the instrument used was a questionnaire of 10 questions with multiple choice. After obtaining the results, it is concluded that the proposal is totally favorable and focuses on the quality of learning, since it is a tool that allows the design, accessibility, interactivity and organization of content, as in the teaching guide "Exploring Plant Life" that contains: objectives of each topic, conceptual map, activities, glossary and evaluations that are created to review the topics of the subject of Plant Biology, which facilitates comprehension, generating active participation of students and helping to achieve meaningful learning.